Lipopolysaccharide in Bile Promotes the Neutrophil Extracellular Traps-Induced Gallstone Formation by Activating the Gallbladder Immune Barrier - Yu J; Meng Z; Liu X; Zheng Y; Xue D; Hao C; Wang L (ImmunoTargets and Therapy)
Jingjing Yu,1,2,* Ziang Meng,1,2,* Xuxu Liu,1,2 Yi Zheng,1,2 Dongbo Xue,1,2 Chenjun Hao,1,2 Liyi Wang1,2 1Department of General Surgery, The First Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, 150001, People’ s Republic of China; 2Key Laboratory of Hepatosplenic Surgery, Ministry of Education, The First Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, 150001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chenjun Hao; Liyi Wang, Email haochenjun@hrbmu.edu.cn; wangliyi_sol@163.comBackground: Cholelithiasis areis a common digestive system disorder, with cholesterol gallstones being the most prevalent type. Gallstones lead to many severe complications, posing a significant burden on global healthcare systems. Many studies have shown associations between biliary microbiota, gallbladder immune microenvironment, and gallstone formation. However, the specific immune mechanisms underlying the cholesterol gallstone formation have not been fully elucidated.Methods: In this study, gallbladderand bile samples from 8 asymptomatic patients with cholelithiasis undergoing cholecystectomy and 11 healthy liver transplant donors were collected for tissue transcriptome sequencing and differential analysis. Male C57BL/6J mice were fed a normal or lithogenic diet for 6 weeks. Starting from the third week, lipopolysaccharide (LPS) or specific regulators were injected intraperitoneally once a week for a total of 3 times. Enzyme-linked immunosorbent assay, quantitative polymerase chain reaction, Western blot, immunohistochemistry, and immunofluorescence were employed for quantitative, qualitative or localization analysis of LPS, neutrophil extracellular traps (NETs), inflammatory factors, proteins, and mRNAs using samples collected from mice.Results: In patients with cholelithiasis, the gallbladder mechanical barrier is impaired, resulting in an immune-activated state. LPS induces damage to the gallbladder mucosal mechanical barrier through the Toll-like receptor 4 (TLR4)/myeloid differentiation factor 88 (MyD88)/nuclear factor kappa-B (NF-κB) signaling pathway. Furthermore, it stimulates the continuous production of NETs through the TLR4/Phosphoinositide 3-kinase (PI3K)/Protein kinase B (Akt) signaling pathway, aggravating the formation of gallstones.Conclusion: With the biliary dysbiosis, excessive LPS can invade the submucosa of the gallbladder, leading to chronic inflammation that recruits neutrophils to form NETs, which are ultimately expelled into bile, thereby promoting the formation of gallstones. Keywords: gallstone, lipopolysaccharide, immune barrier, neutrophil extracellular traps